Effect of metal ions on diphtheria toxin production. - Groman, N (1979)
The effect of several metal ions on the production of diphtheria toxin was tested. By using the gel immunodiffusion system for detecting toxin, a wide range of metal ion concentrations was conveniently surveyed. Five divalent cations, Fe2+, Cu2+, Co2+, Ni2+, and Mn2+ inhibited toxin production within a range of concentrations that did not inhibit growth of the producing strain. Growth and toxin production were inhibited at identical concentrations by both Cd2+ and Zn2+, whereas Al3+ and Sr2+ affected neither growth nor toxin production over the range of concentrations tested. The data showed that Fe2+ was the most effective inhibitor on an equivalence basis, followed by Cu2+, Co2+, and Ni2+ in descending order. All eight strains of Corynebacterium diphtheriae chosen from diverse ecological origins responded similarly to all metals at similar concentrations. A mutant strain which produces toxin at Fe2+ concentrations 500 times greater than are inhibitory for the parent strain had simultaneously acquired resistance to inhibitory concentrations of Cu2+, Co2+, Ni2+, and Mn2+. This suggests that there is at least one common point in the activity of all these metal ions, and that toxin may respond broadly to changes in metal ion concentrations in the environment.